Mental health in biathlon: the role of the coach - Currie, A. (Journal of Biathlon Coaching, 2025)
With the acknowledgment of athlete mental health concerns in elite sports comes a recognition of the need to respond. Supporting athlete mental health involves everyone and there are many parallels with how the physical health and well-being of athletes is supported. This starts with creating an environment that will look after health in support of supreme performance and extends to early recognition of emerging concerns; finding the right and best treatments; and rehabilitation to return to the high-performance arena (Currie and Johnston, 2016).